Anti-PD-1-based immunotherapy as curative-intent treatment in dMMR/MSI-H rectal cancer: A multicentre cohort study. (October 2022) - Wang, Qiao-Xuan; Xiao, Bin-Yi; Cheng, Yong; Wu, Ai-Wen; Zhang, Tao; Wang, Hui; Zhang, Xuan; Huang, Wei-Xin; Tang, Jing-Hua; Jiang, Wu; Steele, Scott R.; Krishnamurthi, Smitha; et al.
Abstract: Background: In a portion of patients with DNA mismatch repair-deficient (dMMR)/microsatellite instability-high (MSI-H) rectal cancer, clinical complete response (cCR) could be achieved after anti-programmed cell death protein 1 (anti-PD-1) immunotherapy. However, no data are available concerning the safety of omitting surgery and adopting immunotherapy as a curative-intent treatment for these patients. Methods: We retrospectively collected a series of patients with dMMR/MSI-H rectal adenocarcinoma who had cCR after receiving anti-PD-1 immunotherapy and adopted immunotherapy as curative-intent treatment from six institutions. Survival outcomes were analysed using the Kaplan–Meier method. Results: Nineteen patients were included with a median age of 48 (range 19–63). One patient was diagnosed with stage I disease, four with stage II disease and fourteen with stage III disease. Sixteen patients received anti-PD-1 immunotherapy as the first line of therapy, and eleven patients were treated with single-agent anti-PD-1 antibodies. The median time from the start of treatment to cCR was 3.8 (range 0.7–6.5) months. During a median follow-up of 17.1 (range 3.1–33.5) months since achieving cCR, no local or distant relapse was observed. Two-year local recurrence-free survival, distant metastasis-free survival, disease free-survival and overall survival for the whole cohort were 100%, 100%, 100% and 100%, respectively. Conclusions: For patients with dMMR/MSI-H locally advanced rectal cancer who achieved cCR during anti-PD-1 immunotherapy, adopting immunotherapy as curative-intent treatment might be an alternative option. Longer follow-up and larger cohorts are warranted to verify this innovative treatment approach. Highlights: Anti-PD-1 antibody demonstrates curative efficacy in dMMR/MSI-H rectal cancer. Anti-PD-1 monotherapy might be sufficient at locally advanced stage. The time and cycle needed for patients to reach cCR varied.